Physiological and biomechanical responses to running on lower body positive pressure treadmills in healthy populations - Farina, K. A.; Wright, A. A.; Ford, K. R.; Wirfel, L. A.; Smoliga, J. M. (Sports Medicine, 2017)
Background: Lower body positive pressure treadmills (LBPPTs) aim to reduce musculoskeletal loading during running. As LBPPTs have become more commercially available, they have become integrated into athletic performance and clinical rehabilitation settings. Consequentially, published research examining the biomechanical and physiological responses to unweighted running has increased.